The DNA dioxygenase Tet1 regulates H3K27 modification and embryonic stem cell biology independent of its catalytic activity. Issue 6 (12th February 2022) - Chrysanthou, Stephanie; Tang, Qin; Lee, Joun; Taylor, Samuel J; Zhao, Yilin; Steidl, Ulrich; Zheng, Deyou; Dawlaty, Meelad M
Abstract: Tet enzymes (Tet1/2/3) oxidize 5-methylcytosine to promote DNA demethylation and partner with chromatin modifiers to regulate gene expression. Tet1 is highly expressed in embryonic stem cells (ESCs), but its enzymatic and non-enzymatic roles in gene regulation are not dissected. We have generated Tet1 catalytically inactive ( Tet1 m/m ) and knockout ( Tet1 −/− ) ESCs and mice to study these functions. Loss of Tet1, but not loss of its catalytic activity, caused aberrant upregulation of bivalent (H3K4me3 + ; H3K27me3 + ) developmental genes, leading to defects in differentiation. Wild-type and catalytic-mutant Tet1 occupied similar genomic loci which overlapped with H3K27 tri-methyltransferase PRC2 and the deacetylase complex Sin3a at promoters of bivalent genes and with the helicase Chd4 at active genes. Loss of Tet1, but not loss of its catalytic activity, impaired enrichment of PRC2 and Sin3a at bivalent promoters leading to reduced H3K27 trimethylation and deacetylation, respectively, in absence of any changes in DNA methylation. Tet1 −/−, but not Tet1 m/m, embryos expressed higher levels of Gata6 and were developmentally delayed. Thus, the critical functions of Tet1 in ESCs and early development are mediated through its non-catalytic roles in regulating H3K27 modifications to silence developmental genes, and are more important than its catalytic functions in DNA demethylation.